Evaluating glial and neuronal blood biomarkers GFAP and UCH-L1 as gradients of brain injury in concussive, subconcussive and non-concussive trauma: a prospective cohort study. Issue 1 (25th August 2019) - Papa, Linda; Zonfrillo, Mark R; Welch, Robert D; Lewis, Lawrence M; Braga, Carolina F; Tan, Ciara N; Ameli, Neema J; Lopez, Marco A; Haeussler, Crystal A; Mendez Giordano, Diego; Giordano, Philip A; Ramirez, Jose; et al.
Abstract : Objectives: To evaluate the ability of glial fibrillary acidic protein (GFAP) and ubiquitin C-terminal hydrolase (UCH-L1) to detect concussion in children and adult trauma patients with a normal mental status and assess biomarker concentrations over time as gradients of injury in concussive and non-concussive head and body trauma. Design: Large prospective cohort study. Setting: Three level I trauma centres in the USA. Participants: Paediatric and adult trauma patients of all ages, with and without head trauma, presenting with a normal mental status (Glasgow Coma Scale score of 15) within 4 hours of injury. Rigorous screening for concussive symptoms was conducted. Of 3462 trauma patients screened, 751 were enrolled and 712 had biomarker data. Repeated blood sampling was conducted at 4, 8, 12, 16, 24, 36, 48, 60, 72, 84, 96, 108, 120, 132, 144, 156, 168 and 180 hours postinjury in adults. Main outcomes: Detection of concussion and gradients of injury in children versus adults by comparing three groups of patients: (1) those with concussion; (2) those with head trauma without overt signs of concussion (non-concussive head trauma controls) and (3) those with peripheral (body) trauma without head trauma or concussion (non-concussive body trauma controls). Results: A total of 1904 samples from 712 trauma patients were analysed. Within 4 hours of injury, there were incremental increases in levels of both GFAP and UCH-L1 from non-concussive body trauma (lowest), to mild elevations in non-concussive head trauma, to highest levels in patients with concussion. In concussion patients, GFAP concentrations were significantly higher compared with body trauma controls (p<0.001) and with head trauma controls (p<0.001) in both children and adults, after controlling for multiple comparisons. However, for UCH-L1, there were no significant differences between concussion patients and head trauma controls (p=0.894) and between body trauma and head trauma controls in children. The AUC for initial GFAP levels to detect concussion was 0.80 (0.73–0.87) in children and 0.76 (0.71–0.80) in adults. This differed significantly from UCH-L1 with AUCs of 0.62 (0.53–0.72) in children and 0.69 (0.64–0.74) in adults. Conclusions: In a cohort of trauma patients with normal mental status, GFAP outperformed UCH-L1 in detecting concussion in both children and adults. Blood levels of GFAP and UCH-L1 showed incremental elevations across three injury groups: from non-concussive body trauma, to non-concussive head trauma, to concussion. However, UCH-L1 was expressed at much higher levels than GFAP in those with non-concussive trauma, particularly in children. Elevations in both biomarkers in patients with non-concussive head trauma may be reflective of a subconcussive brain injury. This will require further study.